2022
DOI: 10.1007/s00217-022-04147-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal and ultrasound treatments on denaturation and allergenic potential of Pru p 3 protein from peach

Abstract: The effect of thermal and ultrasound treatments on denaturation and allergenicity of Pru p 3, the major peach allergenic protein, was determined. The degree of denaturation of Pru p 3 was estimated by sandwich ELISA using specific rabbit IgG, that was previously developed. Validation of ELISA test showed high sensitivity and specificity, and acceptable results of precision and robustness. Allergenicity of Pru p 3 was determined by immunofluorescent assay using three pools of sera from peach allergic individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…HIU treatment for 16 min caused a 50 % reduction in kiwifruit allergen Act d2 and improved in vitro digestibility by up to 62 %. Similarly, HIU treatment also decreased the solubility of kiwifruit total proteins by 20 % [121] .…”
Section: Role In Protein Allergenicitymentioning
confidence: 92%
“…HIU treatment for 16 min caused a 50 % reduction in kiwifruit allergen Act d2 and improved in vitro digestibility by up to 62 %. Similarly, HIU treatment also decreased the solubility of kiwifruit total proteins by 20 % [121] .…”
Section: Role In Protein Allergenicitymentioning
confidence: 92%
“…Tobajas et al. (2023) investigated the impact of ultrasound treatment on the denaturation and allergenicity of Pru p 3, the primary protein responsible for peach allergy, using sandwich ELISA. The researchers found that ultrasound treatments resulted in the denaturation of up to 60% of Pru p 3, with the extent of denaturation primarily influenced by the amplitude and pressure applied.…”
Section: Influence Of Processing Techniquesmentioning
confidence: 99%
“…Generally, nonthermal processing could induce an increase, decrease, or negligible effect on the allergenicity of various fruits allergens depending on the food processing technologies, the nature of proteins, and the test techniques. Tobajas et al (2023) investigated the impact of ultrasound treatment on the denaturation and allergenicity of Pru p 3, the primary protein responsible for peach allergy, using sandwich ELISA. The researchers found that ultrasound treatments resulted in the denaturation of up to 60% of Pru p 3, with the extent of denaturation primarily influenced by the amplitude and pressure applied.…”
Section: Nonthermal Processingmentioning
confidence: 99%